Handbook to exegesis of the New Testament - Porter, Stanley E. (New testament tools and studies, 1997)
This handbook provides a substantial theoretical and practical guide to the multi-faceted discipline of exegesis of the New Testament. After an introduction to exegesis and a bibliographic essay on the basic tools, the volume has two major parts. The first focuses on method, and includes essays on the major approaches to exegesis, including textual criticism, language, genre and backgrounds. The second part applies exegetical method to the various literary units of the New Testament. Most exegetical handbooks are either too short and brief, thereby failing to cover the requisite current topics in sufficient depth, or too technically difficult, failing to provide a useful methodology. This coordinated volume offers succinct and well-informed essays, with plenty of bibliography, written by experts in their respective fields. The handbook will serve well as a textbook, as well as a reference book to the major tools and topics in the area.